Deciding children's futures : an expert guide to assessments for safeguarding and promoting children's welfare in family court - Scaife, Joyce, 1950- (Routledge, 2013)
"Deciding Children's Futures addresses the thorny task of how to assess parents and children who belong to struggling families where there are issues of neglect or significant harm, and when separating parents are contesting arrangements for the care of their children. This is a practitioner's guide: it discusses how to create relationships that are capable of breaching natural parental defences to assessment; the importance of keeping an open mind, how to ask questions that fathom people's experiences, and how to develop understanding of their histories, narratives, worries, hopes and fears. Joyce Scaife's approach draws on practice knowledge, theory and research findings with a view to integrating the accounts of parents and children with safeguarding imperatives and government guidance, thereby enabling professionals to make informed decisions designed to impact positively on children's futures. This accessible and comprehensive book will be of great interest to 'expert' witnesses, practising social workers, children's guardians, solicitors, barristers, magistrates and mental health professionals"--Provided by publisher.